The apparent and potential effects of climate change on the inferred concentration of dissolved organic matter in a temperate stream (the Malse River, South Bohemia) - Hejzlar, Josef; Dubrovský, Martin; Buchtele, Josef; Růzicka, Martin (The Science of the total environment, 2003)
Long-term and seasonal changes in concentration of dissolved organic matter (DOM) and their possible drivers were evaluated for an upland stream in central Europe during 1969-2000. Two periods have been detected within this data set-years with decreased DOM until the middle of 1980s and then years with increased DOM until 2000. Temperature, hydrological regime of runoff from the catchment (namely the amount of interflow), and changes in atmospheric deposition of acidity coincided with the variations in DOM concentrations. The analysis of single runoff events confirmed the relation between the export of increased DOM concentrations from the catchment and interflow. A multiple linear regression model based on monthly averages of temperature and interflow explained 67% of DOM variability. This model suggested a 7% increase in DOM concentration under the scenarios of possible future climate change related to doubled CO(2) concentration in the atmosphere. The scenarios were based on results of several global circulation models.